Effect of oleo chemical waste as partial sand replacement in sand brick - Muhammad Nuraiman, Jumain (2019)
This paper presents about the utilization of oleo chemical waste as a partial sand replacement in sand brick. Due to the growth in terms of development of construction industry, demand of construction material such as brick and material of sand are higher. Brick plays important role in construction as an alternatives of stones and are formed in various classes, types, materials and sizes in large quantity which different in time period and region. The used of sand become uncontrolled and lead to the increasing of sand mining. This activity caused the destruction in environment. Thus created a need for the development material with a suitable utilization of waste. Sand brick is one of building material that highly used in construction. The used of waste materials in sand bricks can lessen the excessive used of sand and reduce the environmental burden. Oleo chemical waste collected from the Oleo Chemical Industry that processing palm oil. However, it also produces a lot of waste. When the waste from factory released, it will be thrown and placed at the landfills. For avoiding landfills full with the waste, it can be used for a better solution which is by replace the waste with material that used for construction purpose. Moreover, no research have done about replacement of oleo chemical waste in bricks for construction materials. This research will investigate the effect of oleo chemical waste as a partial sand replacement in sand brick. The oleo chemical waste are divided into 0%, 5% and 10% of replacement to the percentage weight of the sand. The oleo chemical waste will be dried and grind smoothly before it use for the sand replacement. Three different test which compressive strength test, flexural strength test and water absorption test be conduct to test the performance of the sand brick with different replacement level of oleo chemical waste at age 7th and 28th days. The results and discussions examined and recorded for result of analysis.